Sociological Foundations of Success of Turkish Tv Soap Operas in the Balkans - Gündüz, Ferhan (2020)
For the last decade, Turkish TV series particularly soap operas have been alluring an increasing rate of viewers both in Turkey and 76 countries around the world, spreading from Latin America to the Far East. This article examines the sociological foundations of high levels of interest in Turkish TV series in the Balkan region since relationships between the Turks and other people in this geographic area have a long history. As well, today’s reflections of this historical relationship date back to the fifth century in so many ways. Turkish TV series have thus captured the social and cultural proximity of individuals living in these two geographies in the best sense and have also raised their awareness in this respect. A total of 15 out of 76 TV series released in Turkey until 2016 have been so far exported to Balkan countries and they have received enough attention. Accordingly, it is of utmost importance to determine the sociological foundations of this development.